Technology Adoption in Democratic Republic of Congo(DRC): An Empirical Study Investigating Factors that Influence Online Shopping Adoption - Audu, Janet (Université d'Ottawa / University of Ottawa, 2018)
The growing popularity of the internet and its activities have opened a wide range of business opportunities especially in terms of e-business. Though, reports show that the adoption rate of e-commerce in developed countries seem to be striving, a lot of developing countries still struggle with slow e-commerce adoption rate. Democratic Republic of Congo (DRC) is one these countries where e-commerce adoption is still in its infant stages. However, because of the recent infrastructure improvements and the growth in telecommunication services in the country, internet penetration, more specifically, mobile Internet penetration is growing at a significantly fast pace. This could mean opportunities for e-business services in DRC. The objective of this research is to investigate the factors that could influence online shopping adoption in DRC. This investigation was carried out by adapting an extended version of the Technology Acceptance Model (TAM). A quantitative approach was used in the collection of data and the data was edited and analyzed using the programming language, R. Also, the analytical techniques used in conducting this research include: Descriptive Statistical Methods (Cross tabulation, frequencies) and inferential Statistical Methods (Logistic Regression, ANOVA and Chi square tests). The results from this research show that contrary to the conceptualized model in the literature review where the main constructs included: Perceived Ease of Use(PEOU), Perceived Usefulness(PU) and Perceived Trust(PT), it appears that Perceived Ease of Use(PEOU) does not have any significance in a user’s intention to shop online(p>0.01). However, this research found that Perceived Usefulness and Perceived Trust have a strong statistical significance to a user’s intention to shop online. Furthermore, we found that Gender, Income and Age do not have any moderating influence on the relationship between a user’s perception and their intention to shop online in DRC. However, when the relationship between VI perception and intention to shop online is moderated by experience, we find that there is a variation between users with prior online shopping experience and those without. While these research findings make for remarkable recommendations on a user’s intention to shop online, we recommend that further research on actual usage of e-commerce be examined in DRC to get a better understanding of consumer online behaviors.
Keywords: E-commerce; M-commerce; E-Commerce Adoption; E-business Technologies; E-business; DRC; Africa; technology; Technology Adoption; Technology Acceptance Model (TAM); perceived Usefulness; Perceived Ease of Use; Perceived Trust